The Effect of Structured Physiotherapy Exerciseprogramme on Lung Function in Industrial Workers - Patil Poonam1, Kanase Suraj B2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Context: Repeated exposure to dusty environment in an industry causes airway diseaseswhich may affect pulmonary function over a period of time. Aim:The effects of structured physiotherapy exercises programme on lung function in sugarcane industrial workersStudy Design: An experimental study was conducted on 60 sugar factory workers at in and around karadarea.Purpose of the study: To find out the effect of structured physiotherapy exercise programme on lung function in industrial workers. MaterialsAnd Methodology: -60workers of age group 20-40 from sugar industry participated in this study. They were bounded in single group. The subjects were scrutinized based on the inclusion criteria. All the subjects signed a consent form prior to participation in the study. Before receiving any intervention, the peak expiratory flow rate and 6min walk test was taken and abdominal strength checked by manual muscle testing of abdominal muscle (graded abdominal muscle testing). After recording the pre-intervention outcome measure,The specific exercise protocol was given to the subjects which was included abdominal muscle exercises (graded abdominal muscle exercises)and 6 minute walk test as exercises purpose and diaphragmatic breathing exercises (10 repetition for 3 sets), segmental breathing exercises (10 repetition for 3 sets), incentive spirometry (20 repetition 5 sets).post treatment outcome measure were performed for peak expiratory flow rate,and abdominal muscle strength and 6 minute walk distance. Statistical analysis was done using paired’ test.Result:In this study pre-intervention peak expiratory flow rate was 290±58.251 and post-intervention peak expiratory flow rate was 307±60.914.In peak expiratory flow rate statistically extremely significant difference and increasing peak expiratory rate post intervention with (p<0.0001) with t=5.633 with 59 degree of freedom.The sixminute walk distance (6mwd) increased from 215 to 297 meter.In the study the pre intervention values of abdominal muscle strength (MMT or grades of abdominal muscle) was 1.63± 0.7357 and post intervention abdominal muscle strength was 2.5± 0.7249.In abdominal muscle strength statistically extremely significant difference and increases abdominal muscle strength with (p<0,0001) with t=11.851 with 59 degree of freedom.Conclusion:-Thus, the above study concluded that a structured exercisesprogramme showed a significant improvement clinically as well as statistically significanton the peak expiratory flow rate and 6-minute walk distance and abdominal muscle strength in the sugar industry workers. Hence it accepts the alternate hypothesis.